Pengembangan Training Kit Selektor Warna Barang menggunakan model ADDIE sebagai Sarana Pembelajaran PLC - Yuanto, Teguh Arik; Sudira, Putu (Department of Electronic and Informatic Engineering Education, Faculty of Engineering, UNY, 2019)
This study aims to (1) realize the design of the item color selector training kit and (2) determine the feasibility of the item color selector training kit. The research uses the ADDIE Models reference, namely: analysis, design, development, implementation, and evaluation. Data collection techniques used were observation and questionnaires. The testing consists of product validation by experts, testing by teachers, and testing by students. The data analysis technique used is quantitative descriptive. The results consist of: (1) item color selector training kit design consisting of training and jobsheets. The training sections include boxes, conveyors, selectors and microcontroller circuits, the jobsheet consists of three learning activities, namely (1) introduction of PLC and training, sorting and calibration, timers and counters. (2) the feasibility level of content validation is 89.39% (very feasible), from construct validation is 91.20% (very feasible) and from the trials students get results of 79.96% (feasible). Based on this percentage, the learning tools for the color selector training kit of goods are suitable for use in the learning process.